Probabilistics finite element analysis of 3d portal frame using ANSYS - Wei, Teo Kah (2015)
In this research, a 3D portal frame was analyzed by manual calculation and also ANSYS program with the probabilistic method. This analysis is to determine the stress, strain, deflection and deformation of the structure. Besides that, the structure is checked accordingly to Eurocode 3 also. Nowadays portal frame is widely used for industrial building. It is very stable in term of everything and low in cost. A 500N/